Business Development Strategy for Rolling Bearing Product and Related Services in Food and Beverage Industry - Santoso, R. Yulianto Hidayat; Lim, Resmana (Jurnal Dimensi Insinyur Profesional, 2023)
In running the business, every company has objective to grow and develop. Each company has different objective and development strategy, but identical in final goal, that is to gain profitable growth. Correct strategy is mandatory in developing business, where each company has its own unique character in term of product and penetrated market. Therefore, proper analysis is required in order to determine the correct business development strategy. Starts from market & customer intelligence, to decide whether the targeted market is potential or not. Continue with competitive position analysis, to evaluate whether the company is competitive or not and define what is needed to improve competitiveness in the market. Bearing X as one of market leader in bearing industry and related service, is developing their business to F&B sector. Writer is assigned as sector manager in the respective sector. Writer is doing market potential and competitive position analysis, to be reference in developing proper strategy development, based on Ansoff Matrix market and product development. Defined strategy also closely related with Bearing X’s Unique Selling Preposition (USP) as well as Total Cost of Ownership (TCO) which is proposed to each customer in F&B sector. Using Fishbone Diagram, Bearing X defines business development strategy and put it in to a roadmap, also plans the required investment in order to achieve the target of this business development.